Biophilic Design in Hospitals: A Narrative Review of Its Impact on Users’ Well-being and Healing Environments - Cormio, Laura; Cannella, Cristian; Cormio, Luigi (British Journal of Healthcare and Medical Research, 2026)
The design of healthcare facilities can influence patients’ emotional state, comfort, and overall hospital experience. In recent years, growing attention has been directed toward architectural strategies that incorporate natural elements to create more supportive clinical environments. Among these approaches, biophilic design has been increasingly explored as a way to reconnect built spaces with nature and promote healthier indoor environments. This narrative review discusses current evidence on the application of biophilic design principles in hospital settings. The literature indicates that integrating elements such as natural light, vegetation, nature-inspired materials, and improved environmental conditions may contribute to the development of more supportive and restorative healthcare environments. These features have been linked to lower stress levels, improved psychological well-being, and more positive patient experiences during hospitalization. Nature-oriented design strategies appear, therefore, to offer valuable opportunities for improving the quality of healthcare spaces and supporting both patient recovery and staff well-being.